Marginal Excision as a Surgical Treatment for The Schwannoma of Posterior Aspect of Femur: A Case Report - Raditya, Risang Haryo; Wiratnaya, I Gede Eka (http://dharmais.co.id/, 2024)
Introduction: Schwannoma is a benign nerve sheath neoplasm attached to a peripheral nerve that often develops in the middle-aged population. It usually presents as an asymptomatic mass at first but can be transformed into a pain, swelling, neurologic, or mechanical symptom in several patients. In this study, we are reporting a case of a schwannoma of the posterior aspect of the thigh, in a young adult male. Case Presentation: We reported a 31-year-old male complained of sharp pain, tingling sensation, and mechanical block in the posterior aspect of the right thigh. Radiological imaging showed the tumor of the posterior aspect of the right thigh, with associated soft tissue edema, the cortex is not invaded. Surgical resection was performed on the patient and the tumor was excised with marginal excision surgery technique. Conclusions: The schwannomas of the femur can successfully be excised with no postoperative complications. There is no sign of a recurrent tumor in six months after the procedure.